The Smart Society Between Semantic Indefiniteness and Efficientistic Reductionism - Sessa, Melissa (SocietàMutamentoPolitica, 2023)
The article aims at the construction of an annotated bibliography on the smart society. the impression, and therein lies the cognitive hypothesis, is that the bibliography on the subject is technical and sectoral. the consequences of this technicality and the semantic difficulty that smartness brings, seen to result in a strong impoverishment of the social.